National responses in the context of ASEAN developments over peatfire and haze - Helena , M.V. (2016)
The recent haze episodes of 2013 and 2015 have been especially severe, with serious consequences on the day-to-day lives of Indonesians living closest to the fires and in neighbouring countries. With satellite imagery and news reports pinpointing sustained peatfires as a major source of the haze, national and regional responses have, more than ever, focused on peatlands. At the ASEAN level, ongoing efforts to address peat and haze issues focus around two documents, namely the ASEAN Agreement on Transboundary Haze Pollution (ATHP) 2002 and the ASEAN Peatland Management Strategy (APMS) 2006-2020. This paper analyses the latest national responses within the context of these documents, particularly on the 2013 Haze Monitoring System (HMS) and the soon-to-be-established ASEAN Coordinating Centre for Haze (ACCH). Two responses are of particular interest, namely Singapore’s Transboundary Haze Pollution Bill (THPB) 2014, and Indonesia’s recent ratification of the ATHP. Singapore’s THPB ties in closely to ASEAN’s HMS as it needs accurate land maps so that Singaporean prosecutors can correctly assign blame. The HMS is however constrained as concession maps are available on a case-by-case basis only, which is augmented by Indonesia’s repeatedly delayed One Map Initiative. Indonesia for its part has finally ratified the ATHP and this has renewed regional interest in the establishment of the ACCH in Riau, which, due to its location close to some of the most severe peatfires, is hoped to encourage more local ownership of the issue. However, Indonesia has announced that it needs at least another three years before a marked reduction of haze episodes. Indonesia’s three-year timeline does still fall within the timeframe of the APMS, so the document should be a useful tool to inform developments of Indonesia’s fire and peat policy in the years to come.